Focus Group Discussion Kualitas Air Danau Toba dalam Penentuan Status Trofik Danau Toba - Nita Marikena; Susilawati; Yuli Setiawannie (Yayasan Literasi Sains Indonesia, 2022)
Lake Toba is a tecto-volcanic lake located in the province of North Sumatra, Indonesia. This lake is the largest lake in Indonesia and Southeast Asia (disbudpar, 2019). Lake Toba has ecotourism, namely Leuser National Park and Forest Area with Special Purpose Aek Nauli, Kawasan Strategi Pariwisata Nasional (KSPN)/Kawasan Pengembangan Pariwisata Nasional (KKPN), namely Lake Toba and its surroundings, and Geopark consisting of Toba Caldera Geopark. This is what makes Lake Toba a tourism potential and a direction of development that needs attention. Currently, the Lake Toba Water Quality Standard is set to Class One as contained in the Governor of North Sumatra Regulation Number 1 of 2009 and the trophic status of Lake Toba is Oligotrophic as contained in the Decree of the Governor of North Sumatra Number 188.44/209/KPTS/2017. The determination of the water quality standard of Lake Toba to be Class One as contained in the Governor of North Sumatra Regulation Number 1 of 2009 and the trophic status of Lake Toba is Oligotrophic as contained in the Decree of the Governor of North Sumatra Number 188.44/209/KPTS/2017 currently does not meet. The purpose of this Focus Group Discussion (FGD) is to get input from FGD participants regarding the water quality and trophic status of Lake Toba. The method implemented is in the form of discussion that discusses the quality of water in Lake Toba. Based on the results of the Focus Group Discussion (FGD), the water quality of Lake Toba leads to the Class Two quality standard and the Trophic Status of Lake Toba leads to Mesotrophs. This is influenced by human activities around the Lake Toba area and natural factors. The impact of decreasing water quality of Lake Toba will be increasingly influenced by the determination of Lake Toba as a Kawasan Strategi Pariwisata Nasional super prioritas. The decline in the water quality of Lake Toba can be managed with the cooperation of all parties, namely the community, businessmen and the government, such as the use of technology, environmental conservation, compliance with permits and others.